Human resource development in a knowledge economy an organisational view - Harrison, Rosemary; Kessels, J. W. M. (Joseph W. M.) 1952- (Palgrave Macmillan, 2004)
Human Resource Development in a Knowledge Economy provides a critical approach to the study of human resource development and emphasizes the need for its effective integration with human resource management, as well as with the strategic management of the organization.